Validation of 1‐year predictive score of long‐term response to interferon‐β in everyday clinical practice multiple sclerosis patients. (6th April 2015) - Romeo, M.; Martinelli, V.; Rodegher, M.; Perego, E.; Maida, S.; Sormani, M. P.; Comi, G.; San Raffaele Multiple Sclerosis Clinical Group
<x xml:space="preserve">Abstract</x> Background and purpose The Rio score (RS) and the modified Rio score (MRS) are two scoring systems that can identify the early predictive factors of disability progression in relapsing−remitting multiple sclerosis (RRMS) patients treated with interferon‐β (IFN‐β). The objective of the study was to validate the usefulness of the RS and MRS in a large cohort of multiple sclerosis patients treated with IFN‐β in daily clinical practice. Methods The analysis included a cohort of RRMS patients treated with different formulations of IFN‐β for at least 1 year. The RS and MRS were used to classify the patients after 1 year of treatment. Multivariate analysis was performed to identify predictive variables of suboptimal response at 5 years, defined as Expanded Disability Status Scale confirmed progression or switching to a second‐line therapy. Results Sixty‐nine of 416 included patients were considered as suboptimal responders at 5‐year evaluation. The possible score range was 0–3. A higher risk of suboptimal response was found for RS and MRS in the presence of ≥2 scores (hazard ratio 3.0, P = 0.002, and hazard ratio 5.0, P < 0.0001, respectively). Conclusions Our study confirmed, in a daily clinical setting, that MRS had a better specificity and accuracy than RS in identifying the patients who will have a poor response to long‐term IFN‐β treatment.